A new stygiobiont species of Macrobrachium (Crustacea: Decapoda: Caridea: Palaemonidae) from an anchialine cave on Miyako Island, Ryukyu Islands - Komai, Tomoyuki; Fujita, Yoshihisa (Zootaxa, 2005)
A new stygiobiont species of the caridean genus Macrobrachium Bate, 1864 is described on the basis of two male specimens from an anchialine cave on Miyako Island, southern Ryukyu Islands. The new species, M. miyakoense, is compared with other five stygiobiont species of the genus characterized by a reduced eye, i.e. M. cavernicola (Kemp, 1924), M. villalobosi Hobbs, 1973, M. acherontium Holthuis, 1977, M. microps Holthuis, 1978, and M. poeti Holthuis, 1984. It is the first representative of stygiobiont species of Macrobrachium from East Asian waters.